Relektura cytatów z Księgi Psalmów w Ewangelii według św. Jana - Sikora, Adam Ryszard (Poznańskie Studia Teologiczne, 2010)
The author of the article analyses eights passages from the Gospel according to St. John which contain quotations from the Book of Psalms. The quotations come from Ps 22,19 (Jn 19,24), Ps 41,9 (Jn 13,18), Ps 69,5 (Jn 15,25), Ps 69,10 (Jn 2,17), Ps 69,28 (Jn 19,28); Ps 78,24 (Jn 6,31), Ps 82,6 (Jn 10,34) and Ps 118,26 (Jn 12,13). As a result of the undertaken inquiry the author states that all the quotations from the psalms were reinterpreted in a specific theological perspective. The author of the Fourth Gospel was not interested in the meaning of the quotations in their original context but rather in the Christological thought embedded in them. From those psalms, read in a Christological key within a new context, emerges an image of Jesus who is the Son of God in an absolute sense (Ps 82,6), the Messianic King (Ps 118,26), who despite unjustified hatred on the part of the world (Ps 69,5), unbelief on the part of some of His interlocutors (Ps 78,24) and His awareness of the hostility of one of His disciples (Ps 41,10), zealously fulfills the Father’s plan (Ps 69,10), surrendering himself to all the humiliations (Ps 22,19) and tribulations of salvific passion (Ps 69,22). It should also be underscored that many exegetes interpret the content of those quotations not merely literally, i.e. by linking them to historical events, but expound their deeper spiritual sense.